Inclusive Education in Early Childhood Education from Mel Ainscow’s Perspective - Dewi Yunjiati; Ellen Prima (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study discusses inclusive education in Early Childhood Education from the perspective of Mel Ainscow. Inclusive education is an educational approach that provides equal learning opportunities for all children without discrimination, including those with diverse learning needs. The purpose of this study is to describe the concept of inclusive education according to Mel Ainscow and to analyze its implementation in the development of early childhood education. This research employs a qualitative approach using library research methods. The data were collected from various written sources, including books, scientific journals, research articles, and documents related to inclusive education and early childhood education. Documentation techniques were used for data collection, while the data were analyzed through content analysis. The findings reveal that according to Mel Ainscow, inclusive education is a continuous process aimed at increasing the participation of all learners and reducing barriers to learning within educational environments. In the context of early childhood education, inclusive education can be implemented through flexible learning methods, child-friendly learning environments, and active collaboration between teachers and parents in supporting children’s development. The implementation of inclusive education also contributes positively to children’s social and emotional development, as they learn to respect diversity from an early age. However, several challenges remain, including limited facilities, insufficient teacher competence, and a lack of public understanding regarding inclusive education. Therefore, collaboration among schools, families, and the government is necessary to create an inclusive, equitable, and diversity-respecting early childhood education system.